2021
DOI: 10.1111/oik.08175
|View full text |Cite
|
Sign up to set email alerts
|

Observing frugivores or collecting scats: a method comparison to construct quantitative seed dispersal networks

Abstract: Mutualistic interactions form the basis for many ecological processes and are often analyzed within the framework of ecological networks. These interactions can be sampled with a range of methods and first analyses of pollination networks sampled with different methods showed differences in common network metrics. However, it is yet unknown if metrics of seed dispersal networks are similarly affected by the sampling method and if different methods detect a complementary set of frugivores. This is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 54 publications
(85 reference statements)
0
34
0
Order By: Relevance
“…They produce red (n = 4) or black (n = 5) fruits and their fruiting season starts in June (P. padus and R. spicatum) and ends in October (E. europaeus). The seeds of these plants are dispersed by many different animal species (Supplementary Table 2), including at least 10 mammalian and 31 avian frugivores (Albrecht et al, 2013;Jaroszewicz et al, 2013;Schlautmann et al, 2021). However, the contribution of these species to the total seed dispersal of the plant community in the Białowieża Forest is highly heterogeneous, as only five bird species, i.e., Erithacus rubecula (European robin), Sylvia atricapilla (Eurasian blackcap), S. borin (garden warbler), Turdus merula (common blackbird), T. philomelos (song thrush) and one mammal, the European pine marten Martes martes, account for 97.0% of the fruit removal interactions and 98.6% of the seed rain (Schlautmann et al, 2021).…”
Section: Study Area and Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…They produce red (n = 4) or black (n = 5) fruits and their fruiting season starts in June (P. padus and R. spicatum) and ends in October (E. europaeus). The seeds of these plants are dispersed by many different animal species (Supplementary Table 2), including at least 10 mammalian and 31 avian frugivores (Albrecht et al, 2013;Jaroszewicz et al, 2013;Schlautmann et al, 2021). However, the contribution of these species to the total seed dispersal of the plant community in the Białowieża Forest is highly heterogeneous, as only five bird species, i.e., Erithacus rubecula (European robin), Sylvia atricapilla (Eurasian blackcap), S. borin (garden warbler), Turdus merula (common blackbird), T. philomelos (song thrush) and one mammal, the European pine marten Martes martes, account for 97.0% of the fruit removal interactions and 98.6% of the seed rain (Schlautmann et al, 2021).…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…We summarized the community-wide trait variation in the fruit diameter of plants and the gape width of frugivores at the species level (Figure 1). Frugivores were defined as all animal species recorded eating fruits of any of the studied plant species at least once, either during fruit removal observations in 2011/2012 (Albrecht et al, 2013) or based on the seeds found in the scat of animals collected in 2016-2018 (Schlautmann et al, 2021). Because we did not have direct measures of the gape widths of mammals, a cut-off was set at 2 cm.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations